Serum cytokine levels in patients with acute alcohol heart pathology - V. V. Gorbunov; A. V. Govorin; S. A. Alekseev (Кардиоваскулярная терапия и профилактика)
Aim. To investigate cardiohemodynamic parameters and serum cytokine levels in patients with severe alcohol intoxication (AI). Material and methods. In total, 100 patients with severe AI were examined. All participants underwent 24-hour electrocardiogram (ECG) monitoring, echocardiography (EchoCG), and measurement of serum pro-inflammatory cytokine levels . Results. In patients with severe AI, acute alcohol heart damage (AAHD) was diagnosed relatively often (31.4%). Among these individuals, EchoCG disturbances and increase in serum cytokine levels were maximal. Conclusion. In patients with AAHD, complicated by fatal arrhythmias, pro-inflammatory cytokine synthesis was increased, comparing to arrhythmia-free patients. Maximal cytokine concentration was registered in patients with systolic and/or diastolic left ventricular dysfunction.